Health and wellness tourism: developing a framework for muslim-friendly spa operations - Iylia Syazana, Azman (2025)
The Muslim-friendly spa emerged as an innovative niche sector within the hospitality and tourism industry, distinct from conventional spas due to its adherence to Shari’ah principles. Despite its growing presence, there was a lack of comprehensive guidelines for establishing such spas, as the sector was still in its developmental phase. This study aimed to bridge that gap by crafting a framework for implementing Muslim-friendly spa operations. To achieve these objectives, this study employed Leiper’s Tourism System (1979) to explore the implementation, characteristics, and services that define these establishments, recognizing their appeal as crucial attractions for Muslim tourists. This study selected twelve experienced spa operators from Peninsular Malaysia, with three each from the North, South, East, and Central regions. The selection criteria included Malaysian ownership, over seven years of operation, a diverse range of wellness services, and active online promotion of Muslim-friendly offerings, highlighting their expertise and dynamism. Through indepth interviews, this study gathered rich qualitative data, which was transcribed using NVIVO and analysed by identifying relevant sub-themes. The findings revealed significant issues, including high financial costs, guideline inconsistencies, and difficulties sourcing Halal-certified products. However, the importance of gender-segregated facilities, Shari’ah-compliant operations, and personalized customer consultations was also emphasized. The study produced a detailed framework to guide the implementations of Muslim-friendly spas, offering actionable recommendations for improving operational efficiency and adherence to Islamic principles. It also highlighted the need for consistent regulations and standardized guidelines to address inconsistency across regions and support the sector’s growth. This research provides critical insights for spa operators, policymakers, and stakeholders, contributing to the understanding of the Muslim-friendly spa industry. It also offers opportunities for future studies to examine customer perspectives and economic impacts, enhancing the sector’s role in Islamic tourism and wellness. By addressing key operational issues and proposing practical solutions, the study bridges a critical gap in the literature and supports the sustainable development of the Muslim-friendly spa industry.